Rebel Life: The Life and Times of Robert Gosden, Revolutionary, Mystic, Labour Spy - Mouat, Jeremy (Labour / Le Travail, 2001)
The article reviews the book, "Rebel Life: The Life and Times of Robert Gosden, Revolutionary, Mystic, Labour Spy," by Mark Leier.